Wahbah Az-Zuhaili's Interpretation of the Iron Verses and Their Relevance to the Development of Modern Science - Erviana Khairunnisa; Septiawadi Septiawadi; Ahmad Muttaqin (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2026)
This study aims to analyze the thoughts of Wahbah Az-Zuhaili in Tafsir Al-Munir regarding verses about iron and its relevance to the development of modern science. The study focused on four groups of verses, namely Surah Al-Isra': 50, Al-Kahf: 96, Saba': 10–11, and Al-Hadid: 25, which were selected based on their relationship with the theme of metal materials, the process of processing iron, the strength of materials, and their useful function for human life. This research uses a qualitative approach with library research and thematic analysis (maudhu'i). To minimize subjectivity in connecting interpretation and science, this study limits the analysis to conceptual and correlative aspects, not to claims of direct scientific proof of Qur'anic verses. The data was analyzed through the interpretation of the text of the interpretation of Wahbah Az-Zuhaili which was then compared contextually with scientific findings in the field of modern metal materials and technology. The results of the study show that Wahbah Az-Zuhaili's interpretation of iron verses contains functional meanings related to the strength, flexibility, and use of metals in human life. The concept has relevance to the development of modern technologies, although the relationships found are inspiring-conceptual, not scientific causality. This study concludes that the verses about iron in the Qur'an can be understood as a source of ethical-intellectual value and inspiration in the development of material science and technology, as well as showing the contribution of the integrative interpretation of Wahbah Az-Zuhaili in building a dialogue between Islamic studies and modern science.